Aktualisasi Keteladanan Orang Tua dan Fungsi Rumah Tangga dalam Mengantisipasi Dekadensi Moral Generasi Muda - Suaidi Suaidi (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Family is the most important part of human life. Outwardly, every human being aspires to form a family consisting of human parts bound in a marriage bond which is then called a household. The core purpose of forming a family is to create a more focused human life and provide benefits for the lives of other humans. Before humans develop in life and larger relationships in society and even the country, they are very much determined by family life. If family life is good and patterned with the mission and goals of the family. Then, children who come from good families will become good future generations, and vice versa. In essence, the family greatly determines human development in their lives in the midst of society. This study will provide an overview of how a husband and wife should instill good character for the development of their children through education instilled in the family. Thus, the good and bad of a family can be seen from the children who are raised in the family in question.